PENGARUH LABA KOTOR, LABA OPERASI, DAN LABA BERSIH TERHADAP ARUS KAS - Fetriyani, Ayu Nur; Sri Widiawati, Hestin; Kurniawan, Andy (Prosiding Seminar Nasional Manajemen, Ekonomi dan Akuntansi, 2022)
This study was conducted with the aim of knowing gross profit, operating profit and net income have a significant effect on cash flow . The hypothesis was tested using multiple linier regession techniques assisted by Microsoft Excel 2013 and SPSS Version 24 software. The method used was a quantitave approach with secondary data, namely the financial statement of manufacturing companies for 2019-2021. The population in this study are manufacturing companies listed on the Stock Exchange with a population of 82 companies. The sample testing technique used in this research is purposive sampling. The results of this study are gross profit partially significant effect on cash flow, operating profit partially significant effect on cash flow and net income partially significant effect on cash flow. Meanwhile, gross profit, operating and net profit simultaneously affect cash flow.